Тональные характериcтики монологической и полилогической уcтной речи (на материале современного английского языка) - Анусас, Пятрас (Kalbotyra, 1983)
The article reports an experimental study of some prosodic (pitch) features of two forms of speech, i. e., monologue and polylogue.The data obtained suggest that the difference between the pitch organization of the two forms of speech can be described in terms of pitch levels and pitch configurations, i. e. relative pitch level, pitch range, pitch interval as well as direction of pitch movement.The investigation has clearly revealed that utterances in polylogue have a more complex and unpredictable pitch contour than those in monologue.